2015
DOI: 10.5530/ijper.49.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Scope of Mix-method studies in Pharmacy Practice Research

Abstract: Conducting pharmacy practice research is particularly challenging owing to the varied approaches and methods available. While quantitative methodology has been traditionally endorsed as the more scientific method of research, there is a growing recognition for qualitative inquiry in the field of pharmacy practice research in the past few decades. Hence, the scope of this paper is to provide an overview on how to apply mixed methodology in pharmacy practice research and to discuss some of the benefits and chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…The majority of the pharmacy related research use methods to quantify phenomena, associations or relationships between variables. Therefore, understanding various statistical procedures employed is important to interpret the findings [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the pharmacy related research use methods to quantify phenomena, associations or relationships between variables. Therefore, understanding various statistical procedures employed is important to interpret the findings [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peers and lecturers can help those students who have anxiety towards research by helping them understand the learning process. Studies have shown that academic support, academic effort, and self-efficacy are significantly and negatively correlated with research anxiety [ 45 , 54 57 ]. However, in this study, self-efficacy did not moderate the effect of the research anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The results were similar with that conducted with other innovations, such as modification of laboratory experiment, [32][33] integration of learning media and multimedia, 6 and the development of learning method, 9 as innovation can bring learning activity more efficient and it was effective to build professional skills. 7,34 Cooperative learning applied by the students to complete the given tasks has also proved to be a good strategy for teaching science, 16 while the implementation of inquiry-based learning, 19 Problem-Based Learning, 35 mini research [36][37] through their tasks have become good strategies for chemistry, pharmacy and other relevant sciences teaching. Stoichiometry topic is one of the challenging subjects to learn in Chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…[3] To conclude, mixed-methods research has a potential to generate more complete and higher quality data in pharmacy practice research. [4] However, equal grasp on both methods is required, and the approach is embedded with numerous challenges which should be duly addressed by the researchers prior to making a decision to use this approach. [5] Mudassir Anwar …”
Section: Mixed-methods Research In Pharmacy Practice and Its Implicatmentioning
confidence: 99%